THE COMPETENCE-BASED FOCUSED FORMS OF ESTIMATION OF PROFESSIONAL FOREIGN-LANGUAGE COMMUNICATIVE COMPETENCE (CRITERIA ESTIMATION) - I. A. Mazaieva (Vestnik MGIMO-Universiteta)
The article contains a description of an experimental criterion referenced assessment marking schemes design based on the theory of the socio-cultural approach to cognitive development (Zimnaya I.A.). The article envisages the progress in ESP writing and speaking skills as a part of cognitive development and suggests a cognitive development oriented progression of communication tasks necessary to reach the required ESP learning outcomes - communicative competence in ESP. It also contains a pedagogical strategy of developing criteria-referenced descriptors of performance assessment which serve as guidelines for teachers as well as a strategy of developing checking lists for students. The article provides some significant insights into the effect of criteria- referenced assessment on teacher and student development.